2016
DOI: 10.1556/0806.44.2016.013
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome variation and HMW glutenins in synthetic hexaploid wheats (Triticum turgidumssp.dicoccum/Aegilops tauschii)

Abstract: Seven synthetic hexaploid wheats (Triticum dicoccum/Aegilops tauschii) were subjected for investigation. Numerical variation of chromosome number in F 1 hybrids between three synthetics and common wheat varieties, was recorded. Hexaploid amphiploids (SHW) formed gametes with aneuploid chromosome number at a frequency of 13.2 and 14.8% as male and female parents, respectively. We speculated that the frequency of aneuploids in the generation might depend on variability of BA u -and D-genomes of synthetic parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Ribeiro et al (2013) reported a new x-type HMW-GS in Portuguese wheat landrace Barbela encoded at the Glu-A1 locus and named it as 1Ax1.1. A little later, this protein was described by Daskalova et al (2016) in three synthetic hexaploid lines (Triticum turgidum ssp. dicoccum/Aegilops tauschii) and their tetraploid wheat parents.…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al (2013) reported a new x-type HMW-GS in Portuguese wheat landrace Barbela encoded at the Glu-A1 locus and named it as 1Ax1.1. A little later, this protein was described by Daskalova et al (2016) in three synthetic hexaploid lines (Triticum turgidum ssp. dicoccum/Aegilops tauschii) and their tetraploid wheat parents.…”
Section: Discussionmentioning
confidence: 99%
“…The total grains analysed in the beginning were 50. Synthetic hexaploid wheat (SHW) 530 was derived by crossing a tetraploid hybrid (45390/45398) to Aegilops tauschii accession 19088 (Daskalova et al, 2016). This research showed that SHW530 included two lines (530-1 and 530-2), differing only at the Glu-B1 locus, and both had a HMW glutenin pair 4t+10.1t.…”
Section: Methodsmentioning
confidence: 99%
“…Bibi et al (2012) showed a range of D-genome-encoded subunits of the Elite-II SHW subset along with superior glutenin alleles in the B-genome (1Bx7+1By8, 1Bx6+1By8 and 1Bx13+1By16). In our previous study (Daskalova et al, 2016), five subunits at the Glu-A1 (1.1), 22) and Glu-D t 1 (2+11, 4+10.1) loci were reported in nine synthetic lines (T. dicoccum/Ae. tauschii), which have not been presented in the publications for SHW till now.…”
Section: Introductionmentioning
confidence: 92%
“…It is possible to increase the yield of cultivated crops by investing additional funds for the application of new effective cultivation technologies, high-yielding varieties and hybrids, machinery and equipment for cultivation of crops, fertilizers, means of weed control and protection against pests and diseases, storage and processing of agricultural products, etc., that is, an intensive way of development of the industry [3,4].…”
Section: Introductionmentioning
confidence: 99%